2021
DOI: 10.1111/ane.13445
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal vagal nucleus involvement relates to QTc‐prolongation after acute medullary infarction

Abstract: Background Infarction of the medulla has been associated with prolongation of the QTc, severe arrhythmia, and sudden cardiac death, yet the precise anatomical substrate remains uncertain. Aims We sought to determine the possible anatomical structures relating to QTc‐prolongation in patients with acute medullary infarction. Methods We included 12 subjects with acute ischemic medullary infarction on brain MRI, who presented within 4.5 h from the last known well time, with a 90‐day follow‐up. For an unbiased lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Fourth, altered ECG parameters may be related to autonomic dysfunction, which was common in patients with MCI 27 . Previous research reported a correlation between QT prolongation and dorsal vagal nucleus infarction 28 , which might affect the parasympathetic pathway and dysregulate the automatic neural control of cardiac function 29 . This indicates that prolonged ventricular repolarization may be cerebrogenic arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, altered ECG parameters may be related to autonomic dysfunction, which was common in patients with MCI 27 . Previous research reported a correlation between QT prolongation and dorsal vagal nucleus infarction 28 , which might affect the parasympathetic pathway and dysregulate the automatic neural control of cardiac function 29 . This indicates that prolonged ventricular repolarization may be cerebrogenic arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…al. suggested that long QT syndrome (LQTS, de ned by QT interval >500 milliseconds) in the donor heart was associated with accelerated development of cardiac allograft vasculopathy (CAV), a broproliferative disease causing intimal thickening of coronary vasculature in transplanted heart [16][17][18] . However the underlying molecular changes of LQTS donor myocardial and the molecular mechanisms contributing towards accelerated CAV post-transplant was not elucidated 3,19 .…”
Section: Introductionmentioning
confidence: 99%